Gambaran status kebersihan gigi dan mulut pada pengidap HIV/AIDS di Yayasan Batamang Plus Manado - Putrawan, I Putu G.E.; Suling, Pieter L.; Mintjelungan, Christy N. (Universitas Sam Ratulangi, 2016)
Abstract: Human immunodeficiency virus (HIV) is a virus that attacks the immunity system. Poor oral hygiene could be a major risk of opportunistic infections because HIV weaken the immune system capability to fight and cure any kind of infections. This study was aimed to obtain the dental health status of patients with HIV/AIDS at Yayasan Batamang Plus Manado by using Oral Hygiene Index Simplified (OHI-S). The OHI-S index according to Green and Vermilion is an evaluation by adding the total score of Debris Index (DI) and Calculus Index (CI). This was a descriptive study with a cross-sectional design. Samples were obtained by using purposive sampling technique. There were 30 people as respondents in this study. The result showed that the average of OHI-S score was 2.2 which was categorized as fair according to WHO. Conclusion: The oral hygiene status of patients with HIV/AIDS at Yayasan Batamang Plus Manado was categorized as fair.Keywords: human immunodeficiency virus, oral hygiene.Â Abstrak: Human immunodeficiency virus (HIV) ialah virus yang menyerang sistem kekebalan tubuh manusia. Buruknya status kebersihan gigi dan mulut dapat mengakibatkan rentannya infeksi oportunistik pada rongga mulut karena virus HIV melemahkan kemampuan tubuh dalam melawan infeksi dan penyakit. Penelitian ini bertujuan untuk mengetahui status kebersihan gigi dan mulut pada pengidap HIV/AIDS di Yayasan Batamang Plus Manado yang dinilai dengan Oral Hygiene Index Simplified (OHI-S). Indeks OHI-S menurut Green dan Vermillion merupakan penjumlahan Debris Index (DI) dan Calculus Index (CI). Jenis penelitian ialah deskriptif dengan desain potong lintang. Teknik pengambilan sampel menggunakan purposive sampling dengan jumlah responden sebanyak 30 orang. Hasil penelitian menunjukkan bahwa status kebersihan gigi dan mulut pengidap HIV/AIDS di Yayasan Batamang Plus Manado sebesar 2,2, yang menurut kategori WHO termasuk kategori sedang. Kata kunci: human immunodeficiency virus, kebersihan gigi dan mulut